Influence of cryoprotectant levels on storage stability of surimi from a tropical fish, Nemipterus japonicus (Bloch) and quality of surimi-based products - Parvathy U (Department of Processing Technology, College of Fisheries, 2009)
A study was undertaken with the aim of reducing the concentration of cryoprotectants in surimi without adversely affecting stability of the material during frozen storage. The concentration of sugar in commercially produced surimi is generally about 8% which may result in high sweetness in the products prepared. A tropical fish, Nemipterus japonicus (Bloch) was used as the raw material. Minced fish meat was strained, water leached, mixed with different levels (0%, 2%, 4%, 6% and 8%) of sucrose-sorbitol mixture in 1:1 ratio, quick frozen at -35 oC and frozen stored at -20 oC.